Promoting Autonomous Learning Using Self-Discovery Technique with Self-Prepared Worksheets in Extensive Reading Class - Victa Sari Dwi Kurniati; Kankamon Suthum (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2019)
This research is an action research that investigates the implementation of self-discovery autonomous learning using self-discovery technique with self-prepared worksheet in extensive reading class. The study was conducted in the contexts of a classroom teaching and learning situation. Self-discovery learning is believed to be effective in helping the students to improve their reading skills because this technique forces student to be autonomous learner. The study used action research model by Kemmis and Taggart. However, the researcher does not use cyclic treatment in this study, instead its implemented in one big cycle in one semester. As it is needed to be implemented in the whole semester to get the real result. The autonomous learning using self-discovery technique with self-prepared worksheet in extensive reading class was able to improve the students’ achievement in extensive reading, it is indicated in the post test scores compared to the pre-test score. Nevertheless, there are positives and negative effects found during the acting and observing phase. The positive effects are the students become more active in class, the students can explore the text freely as they like, thus, lead to the students’ better communication. Whereas, the class becomes noisy since the students have to discuss in their group and the lecturer had more burdens in finding, selecting, choosing and providing the text for the class activities. Keywords: autonomous learning, self-prepared worksheet, extensive reading.